A State-of-The-Art Technical Review on Chemically Enhanced Primary Treatment Plant - Chalise, Samundra; Prajapati, Supendra; Yadav, Swadesh Kumar; Chand, Sudip; Gorathoki, Madan; Yadav, Yogesh (Journal of Advanced College of Engineering and Management, 2023)
This review paper aims to provide a comprehensive assessment of chemically enhanced primary treatment (CEPT) processes in wastewater treatment plants (WWTPs). The outdated and ineffective performance of existing treatment plants has raised concerns regarding public health and environmental safety. CEPT has emerged as a promising alternative approach to enhance the efficiency and effectiveness of primary treatment. By adding chemical coagulants or precipitants to the wastewater, CEPT facilitates the aggregation and settling of suspended solids and contaminants, leading to improved treatment outcomes. This review evaluates the performance and effectiveness of different chemical coagulants, including ferric chloride (FeCl3), polyaluminum chloride (PACl), and alum, in terms of their ability to remove various pollutants such as suspended solids, turbidity, organic matter, nutrients, and emerging contaminants. The findings from the reviewed studies indicate that different coagulants exhibit varying efficiencies in removing specific parameters such as turbidity, total suspended solids (TSS), chemical oxygen demand (COD), and phosphorous. Alum, ferric chloride, and ferric sulfate showed effectiveness in tannery wastewater treatment, while PACl maximized the removal of macro pollutants. The use of organic carbon sources and sludge recycling demonstrated cost reductions and improved nutrient removal. CEPT was found to be effective in TSS and BOD removal, potentially allowing for compact treatment facilities and enhancing the capacity of biological treatment units. The utilization of recovered alum from water treatment sludge (WTS) in CEPT showed comparable efficiencies to fresh alum. The paper also identifies research gaps and future directions in the field of chemically enhanced primary treatment, while discussing the challenges and limitations associated with CEPT processes. While the reviewed studies provide valuable insights into the performance of different coagulants and coagulant aids, further research is necessary to assess their long-term effects and cost-effectiveness in large-scale applications. The optimal choice of coagulant depends on specific wastewater characteristics and treatment goals. Understanding and optimizing CEPT processes will contribute to the development of innovative solutions for challenges in wastewater treatment systems caused by urbanization, population growth, and emerging contaminants in the major city like Kathmandu.